2019
DOI: 10.5114/ada.2018.76425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fennel essential oil and trans-anethole on antibacterial activity of mupirocin against Staphylococcus aureus isolated from asymptomatic carriers

Abstract: Introduction Staphylococcus aureus constitutes the most pathogenic species within the staphylococcal genus. Humans remain the major reservoirs of this pathogen which colonizes mostly anterior nares of healthy individuals. Aim To investigate the effect of fennel essential oil (FEO) and trans -anethole ( t A) on antibacterial activity of mupirocin (MUP) against S. aureus strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…This result is in line with those who had investigated phytochemistry, antimicrobial activity and GC-MS of Portuguese fennel fruits that gave very compatible results with the current study where the crude extract has antimicrobial activity slightly lower than those belong to positive standard used; tetracycline as antibacterial and nystatin as antifungal [45]. Also, our finding showed moderate effect of fennel extract against methicillin resistant Staphylococcus aureus (MRSA) clinical isolate and this result is relative to those findings which concluded that the combination between fennel essential oil and mupirocin has a significant eradicating effect against S. aureus and his finding will be useful antistaphylococcal agent [46].…”
Section: Antimicrobial Activity Determinationsupporting
confidence: 87%
“…This result is in line with those who had investigated phytochemistry, antimicrobial activity and GC-MS of Portuguese fennel fruits that gave very compatible results with the current study where the crude extract has antimicrobial activity slightly lower than those belong to positive standard used; tetracycline as antibacterial and nystatin as antifungal [45]. Also, our finding showed moderate effect of fennel extract against methicillin resistant Staphylococcus aureus (MRSA) clinical isolate and this result is relative to those findings which concluded that the combination between fennel essential oil and mupirocin has a significant eradicating effect against S. aureus and his finding will be useful antistaphylococcal agent [46].…”
Section: Antimicrobial Activity Determinationsupporting
confidence: 87%
“…Numerous studies have shown that FV effectively controls a range of infectious disorders of bacterial, fungal, viral, mycobacterial, and protozoal origin. [15][16][17][18][19] Along with the present study, a study in rats showed that treatment with a Cassia obtusifolia L. (CO) and FV mixture has beneficial effects against constipation. 20 In addition, fennel essential oil improves symptoms and the quality of life in patients with irritable bowel syndrome.…”
Section: Introductionsupporting
confidence: 52%
“…This result is in line with those who had investigated phytochemistry, antimicrobial activity and GC–MS of Portuguese fennel fruits that gave very compatible results with the current study where the crude extract has antimicrobial activity slightly lower than those belonging to the positive standard used; tetracycline as antibacterial and nystatin as antifungal [ 51 ]. Also, our finding showed a moderate effect of fennel extract against methicillin-resistant Staphylococcus aureus (MRSA) clinical isolate and this result is relative to those findings which concluded that the combination between fennel essential oil and mupirocin has a significant eradicating effect against S. aureus and his finding will be useful antistaphylococcal agent [ 52 ].…”
Section: Resultsmentioning
confidence: 62%